Paroxysmal Hemicrania-Trigeminal Neuralgia (PH-Tic) syndrome with no structural lesion in a Brazilian woman: the first case-report - Fagundes, Thales Pardini; Hemerly, Matheus Compart; Mangolin, Alison; Carvalho, Ellen Silva de; Silva, Natália de Oliveira; Cetlin, Roberto Satler; Dach, Fabíola (Headache Medicine, 2023)
Introduction In Brazil there is only one case report of a patient diagnosed with Paroxysmal Hemicrania-Trigeminal (PH-Tic) syndrome reported, however it was observed in a patient with Chiari I malformation. Objective Here, we describe the first case of primary PH-Tic syndrome in the country. Method Case report. CARE guideline was used to guide the structuring of this article. This case report was approved by the ethics committee and has been registered under the protocol number 70705623.7.0000.5440 on “Plataforma Brasil”. Results A 72-year-old woman with a five-month history of headaches was admitted at our headache outpatient clinic. The pain was sharp, intense, localized in the periorbital and left temporal regions. Blood counts, liver, renal and thyroid function were normal, as well as brain magnetic resonance imaging. Despite using carbamazepine, the patient had pain in only the left side of the face. Indomethacin was added until the dose of 100 mg a day and resulted in improvement of headache frequency. Conclusion PH-Tic should be hypothesized in patients with short-lasting headaches associated with facial pain that partially improve with carbamazepine or indomethacin.